E-Module Design for Local Wisdom Theme Project in Madrasah Ibtidaiyah - Nurmayuli; Hartati Lubis, Tuti; Sabila, Hidayatis (Dirasah: Jurnal Pendidikan Islam, 2026)
Introduction of local wisdom, by directly socialising it or integrating it into intrakurricular learning or project-based learning. However, some teachers still experience difficulties in designing the integration between learning materials and local wisdom. The purpose of this study is to analyse the needs of Madrasah Ibtidaiyah and to design an e-module for project themes on local wisdom in Madrasah Ibtidaiyah. The research method uses the Addie development model. The study was conducted at MIN 3 in Banda Aceh. The research population includes all stakeholders of MIN 3 schools in Banda Aceh, including the Head of the Madrasah and all the madrasah teachers. The sampling technique uses snowball sampling for teachers and purposive sampling for the Head of the Madrasah. The analysis stage resulted in two analyses of madrasah needs related to local wisdom. The design stage was carried out through discussions with colleagues and FGDs with madrasah teachers. The development stage involved designing. The development stage involved designing the e-module and validating it with 3 validators, and making improvements according to the validators' suggestions, so that the e-module was deemed suitable for use. The implementation stage involved a small-scale trial with a response rate of 87.25%, falling into the very suitable category. During the evaluation stage, a large-scale trial was conducted with a response rate of 87.50%, also falling into the very suitable category.